2021
DOI: 10.3390/ijerph182010830
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Mental Health Impact of COVID-19 on Vulnerable and Non-Vulnerable Groups: A Systematic Review and Meta-Analysis of Observational Studies

Abstract: Vulnerable populations may be more vulnerable to mental health problems posed by the coronavirus disease 2019 (COVID-19) pandemic. A systematic review was performed to compare the mental health impact of COVID-19 between vulnerable and non-vulnerable groups. Five electronic databases were searched for observational studies reporting the psychological outcomes of both vulnerable populations and healthy controls during the COVID-19 era. The primary outcomes are the severity of depression and anxiety, and seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 83 publications
(394 reference statements)
0
19
0
1
Order By: Relevance
“…Similar results were reviewed by Murphy et al [ 142 ], highlighting the exacerbation of symptoms in pre-existing mental health conditions. In contrast with these findings, Nam et al [ 143 ] reported mixed results regarding the mental health impact in vulnerable groups such as people with chronic disease, pregnant women and people with pre-existing mental health conditions. Interestingly, the older segment of the population experienced lower levels of stress, anxiety and depression symptoms.…”
Section: Mental Health During the Pandemicmentioning
confidence: 96%
“…Similar results were reviewed by Murphy et al [ 142 ], highlighting the exacerbation of symptoms in pre-existing mental health conditions. In contrast with these findings, Nam et al [ 143 ] reported mixed results regarding the mental health impact in vulnerable groups such as people with chronic disease, pregnant women and people with pre-existing mental health conditions. Interestingly, the older segment of the population experienced lower levels of stress, anxiety and depression symptoms.…”
Section: Mental Health During the Pandemicmentioning
confidence: 96%
“…The elderly generally experienced significantly lower levels of psychological symptoms including depression, anxiety, and perceived stress. Pregnant women, patients with chronic diseases, and patients with pre-existing severe mental disorders showed mixed results according to each mental health outcome ( 43 ). Across countries, the mental health of unemployed people and those experiencing financial insecurity was worse than that of the general population ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Universities need to guide students to obtain information through authoritative channels to reduce the negative impact of rumors. Second, online psychological counseling and intervention should be actively carried out ( 43 ). In particular, it is necessary to focus on students who are quarantined and students with confirmed cases of the virus around them.…”
Section: Discussionmentioning
confidence: 99%
“…This population is specifically vulnerable for COVID-19 and severe courses including mortality (given the risk factors: physical disease and older age), and for not sufficiently seeking or receiving health care for non-COVID-19 related physical illness (which per definition all of them have). However, studies on distress and mental health of hospital inpatients not admitted for COVID-19 are missing, whereas evidence from studies focusing on populations with chronic diseases remains inconclusive, as was also found in a systematic review comparing the mental health impact of COVID-19 on vulnerable and non-vulnerable groups ( 10 ). While some studies suggest increased prevalence of depression, anxiety, and distress ( 11 , 12 ), others report no indications for an association between mental health and the COVID-19 pandemic on people with pre-existing chronic disease ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%